1984
DOI: 10.1103/physrevlett.52.2375
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of the Increase of the Two-Dimensional Critical Temperature in Multilayer Adsorption

Abstract: Measurements of multilayer adsorption of solid 4 He on graphite have been made for 0.965 K^ T^ 1.24 K at intervals of ~ 15 mK using fourth sound in He II as a probe. The first observation of the increase of the two-dimensional critical temperature T cj with increasing layer number j is reported. We extrapolate our values of T cj for j -• oo and obtain the bulkroughening transition temperature, confirming a prediction of current theories. The modeling of the acoustics including effects of the solid-liquid inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In addition, one can precisely control the density of steps and kinks as a function of pressure and temperature. Previous measurements [11,12] are in excellent agreement with the variational theory of Weeks [13] for multilayer solid absorption and the predicted [14] increase of the two-dimensional critical temperature with increasing layer numbers. In this paper we report a clear observation of a two-stage layering transition which appears at temperatures below 0.95 K and in layers at least as high as the eighth (the highest transition observable in our experiment).…”
supporting
confidence: 80%
“…In addition, one can precisely control the density of steps and kinks as a function of pressure and temperature. Previous measurements [11,12] are in excellent agreement with the variational theory of Weeks [13] for multilayer solid absorption and the predicted [14] increase of the two-dimensional critical temperature with increasing layer numbers. In this paper we report a clear observation of a two-stage layering transition which appears at temperatures below 0.95 K and in layers at least as high as the eighth (the highest transition observable in our experiment).…”
supporting
confidence: 80%
“…One type of transitions is the layering transitions, in which the thickness of a typically solid film increases discontinuously by one layer as the pressure is increased. Such transitions have been observed in a variety of systems including for example 4 He [5] and ethylene adsorbed on graphite [6]. The n-th layering transition from a n À 1 layer film to an n layer film, typically is only present at low temperatures and may terminate as the temperature increases in a layering critical point T cY n aJ which belongs to the universality class of the twodimensional Ising model.…”
Section: Introductionmentioning
confidence: 99%
“…The layering transitions are rounded, probably because the layering transitions have a critical point of order 1 K (see Ref. [27]). By varying the gate voltage, consequently the spring constant, we have confirmed that the variation of the resonance frequency f 0 in Fig.…”
mentioning
confidence: 99%